A revisit at 16 years for individuals from peri-urban New Delhi for tobacco use and associated oral lesions. (8th January 2019) - Mehrotra, Ravi; Nethan, Suzanne Tanya; Ravi, Priyanka; Grover, Shekhar; Sharma, Shashi; Rath, GK; Kaur, Jatinder; Ralhan, Ranju; Srivastava, Anurag
Objectives: India has a high incidence of oral cancer due to multifarious tobacco use. The objective of this study was to assess the status of tobacco-related oral lesions over 16 years, in a screen-detected population. Methods: This cross-sectional study involved home visits of 2000 Delhi residents, previously screened for oral potentially malignant disorders/oral cancer and counseled for tobacco cessation. Their basic demographics and tobacco/alcohol history were noted followed by oral visual examination for any related mucosal abnormalities. The data thus obtained were statistically analyzed. Results: Two hundred and sixty-five individuals (13.2%) could be traced after 16 years. The status of oral lesions varied across the participants, mainly in terms of their location, type, number, and/or presence/absence; no oral malignancies were noted. Most individuals had either a decreased use (34%, p < 0.001) or had quit tobacco (25.7%, p < 0.001); 8.3% individuals from the former and 5.7% from the latter group showed complete lesion(s) regression. The overall change in the tobacco use and oral lesions showed a highly significant positive association ( p < 0.05). Conclusion: A direct relationship exists between tobacco use and oral lesions. Repeated, tobacco cessation counseling provided by health-care professionals is effective. Oral screening of high-risk individuals, along with tobacco cessation, is thus essential.